New distributional records of Hydrophilidae Latreille, 1802 (Coleoptera: Hydrophiloidea) from Brazil. Issue 4 (2nd October 2018) - da Silva, Gizelle Rodrigues; Clarkson, Bruno; Lima, Lucas Ramos Costa
ABSTRACT: A survey of the Hydrophilidae (Coleoptera: Hydrophiloidea) from Baixo Parnaíba Sub-basin, north of Piauí (Northeast Region of Brazil) is provided here. A total of 288 specimens, from 7 genera and 13 species, were collected between January 2015 and March 2016 in 15 localities. Six species are recorded for the first time from the State of Piauí: Berosus firmius Orchymont, 1940; Derallus ambitus Orchymont, 1940; Helochares (Helochares) abbreviatus (Fabricius, 1801); Hemiosus (Hemiosus) mornarius Orchymont, 1940; Hydrophilus ensifer Brullé, 1837 and Enochrus ( Methydrus ) venezuelensis Fernández, 1988. Moreover, the last species aforementioned is recorded for the first time from Brazil.